Prevalence of self-reported systemic arterial hypertension in urban and rural environments in Brazil: a population-based study - Jessica Pronestino de Lima Moreira; José Rodrigo de Moraes; Ronir Raggio Luiz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The aims of this paper were to estimate the prevalence rates of self-reported high blood pressure among adults in urban and rural environments in Brazil and identify possible associations stratified according to household location. Data from the Brazilian National Household Sample Survey (PNAD) was used, incorporating information from the sampling plan. Logistic regression was used to obtain the odds ratio (OR) as a measure of association between variables and the outcome. The prevalence of self-reported high blood pressure in Brazil was 20.9%: 21% in urban areas and 20.1% in rural areas (OR = 1.06). In both areas, the likelihood of reporting high blood pressure increased with age and women, former smokers, migrants and individuals with morbidities, non-white individuals and individuals with health insurance were more likely to report this disease. Also, in both rural and urban areas, prevalence of high blood pressure was lower among workers and decreased with increasing levels of schooling. All variables showed an association with self-reported high blood pressure in both rural and urban areas, but differences in magnitude were observed in relation to sex and age group. These differences could help justify the promotion of better access and intervention methods at prevention clinics for different population groups.